Development and Integration of Microgrids - Cao, Wen-Ping; Yang, Jin (IntechOpen, 2017)
The utilization of AC or DC microgrids across the world has increased dramatically over the years and has led to development opportunities as well as technical challenges when they are connected to the main grids or used as stand-alone systems. This book overviews the development of AC/DC microgrids; explains the microgrid concepts, design and control considerations, discusses operational and technical issues, as well as interconnection and integration of these systems. This book is served as a reference for a general audience of researchers, academics, PhD students and practitioners in the field of power engineering.